The snowman - Ahmad Kamal, Siti Aisyah Mardhiah; Osman, Iffah Su’aidah Nabihah; Khairussaleh, Asmaa’; Mohamad Nizam, Nur Fatin Amirah; Wee, Hassnah (Universiti Teknologi Mara, Kedah, 2022)
It is difficult for travellers to store food and beverages that will keep them warm during their travels. Consequently, the "Snowman" multi-purpose product is created. This product is made of powder-coated stainless steel, a known absorbent substance, thereby preserving the condition of the meal during the journey or work hour. In addition, this innovation offers numerous advantages for users, such as being more practical, convenient, hygienic, and lasting. The product can be placed in the bag and carried. In addition, this product has the potential to be commercialized, as tumblers have recently become popular among younger generations because of their ease. This innovation offers numerous advantages for users, such as being more practical, convenient, hygienic, and lasting. This product has the potential to be commercialized, as tumblers have recently become popular among younger generations because of their ease. This product supports two Sustainable Development Goals of the United Nations, namely excellent health and well-being (SDG3) and industry innovation (SDG9). Therefore, this product would benefit society by encouraging travellers to cook for themselves and take better care of their health.